The reality of using the performance tasks in teaching the curriculum of family education in intermediate grade by female teachers in Hail region - Al-Ayyaki, Kholoud Saleh Rashid (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify the reality of using the performance tasks in teaching the curriculum of family education in middle stage by female teachers in Hail region, in order to achieve this goal the researcher used the descriptive analytical method .She also used a questionnaire (as a main tool of the research), and note card for analyzing the achievement files. She applied all that on a random sample contained 62 female teachers who teach the curriculum of family education for the intermediate grade.The results of this research:1-  the axis of understanding of female teachers who teach the curriculum of family education about the performance tasks and its application has got an average of (2.60 out of 5) (medium) , the axis of the reality of using the performance tasks by female teachers who teach the curriculum of family education has got a medium rate ( 3.68 out of 5) ( high ) .2- the axis of the obstacles which counter applying the performance tasks by the female teachers who teach the family education ( according to the evaluating of female students) has got medium rate (2.34 out of 5) ( medium).3- there were not any significant statistical differences (ɑ ≤ 0.05) at the indicator level among the averages of the responses of study sample in all the axes according to the variables of specialization and experience , and according to the variable of academic qualification in the tow axes ( the limit of understanding the concept of performance tasks and its using by female teachers ,and the obstacles which counter the female teachers during applying the performance tasks).4- there were some differences in the axis of the reality of using performance tasks by female teachers ( with different academic degree bachelor or master degree ,or intermediate degree ) who teach the curriculum of family education during evaluating the female students According to the results, the researcher suggested several recommendations in order to generalize using the approaches of performance tasks in different stages of public education, activating it in all the aspects of performance, and raise awareness about the performance tasks inside the school and in the society.
Keywords: reality; performing tasks; family education course; intermediate teachers; Hail